Analisis Kemampuan Siswa Menyelesaikan Soal Cerita Pada Pembelajaran Matematika Di Kelas IV SDN 9 Bukit Batu Riau - Rizki Wasiah; Gustimal Witri; Zariul Antosa (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
The ability to solve story problems is a skill in solving, answering, and working on questions in accordance with the learning objectives and the intent of the questions. The existence of learning mathematics can improve students' ability to count. One of them is solving story problems. This study aims to describe the ability of grade IV students of SD Negeri 9 Bukit Batu in solving math story problems. The ability to solve story problems is seen from the indicators in solving math story problems, while the indicators are: 1) Ability to write down known aspects, 2) Ability to write down aspects in question, 3) Ability to solve mathematical models, 4) Ability to draw conclusions. The type of research that the researcher will use is descriptive quantitative. Data collection techniques using test techniques, namely in the form of student test results which are then analyzed according to predetermined indicators. Based on the results of the data analysis that has been done, it can be seen from the four indicators that the average value is 63.08. This shows that the ability of grade IV SDN 9 Bukit Batu students is in the sufficient category